Determinación del Estado actual del pavimento articulado de las calles 10 de agosto y guayaquil sector centro histórico de la ciudad de Riobamba para la elaboración de un Plan de Mantenimiento vial. - Aguirre Amaguaya, Juan Pablo (2016)
This research aims to determine the current state in which is articulated pavement of the streets on 10 de Agosto and Guayaquil, the historic downtown area of the city of Riobamba, to develop a maintenance plan that will restore in good condition the pavement of the aforementioned streets, respecting their materials which is designed articulated pavement in this area, considering that are considered part of the cultural heritage of the city. The methodology used for this research is exploratory, descriptive, explanatory. Through this project we have evaluated the two streets with a total of 1985.50 m 1.98 km, 10 August Street: with a length of 996,00 m starting from Alvarado Street to the street and street Carabobo Guayaquil: with 989,50m length starting from Alvarado street to Carabobo street. In the evaluated area has been obtained using the method of Pathologies articulated pavement, the street on August 10 is in a general BAD condition and street Guayaquil REGULAR condition. For the above it is necessary to perform a road maintenance plan that allows the conservation of the road surface, avoiding the total deterioration of the pavement in the streets because they have not previously received any kind of maintenance from their rehabilitation. It added that this proposal will be supported by analysis of unit prices, budgets and schedules for different stages of maintenance in the course of a year established in this investigation.